PENGARUH FAKTOR BUDAYA, SOSIAL, INDIVIDU DAN PSIKOLOGIS TERHADAP KEPUTUSAN KONSUMEN MEMBELI DI INDOMARET - Supriyono .; Dibyo Iskandar (STIE AUB Surakarta, 2015)
This study aims are to investigate the influence of cultural factors, social factors, personal factors and psychological factors on purchase decision in Indomaret Surakarta. Analysis using multiple linear regression, F test, t test, test the coefficient of determination (R2). Multiple linear regression analysis showed that all variables figures obtained positive coefficient. The test results (F) indicates that the variable cultural factors, social factors, personal factors and psychological factors together influence the purchasing decisions in Indomaret Surakarta. T test results showed that the variables of individual factors and psychological factors significantly influence purchasing decisions while variable cultural factors and social factors do not significantly influence the purchasing decision. To test the R2 (coefficient of determination) indicates that the variable cultural factors, social factors, personal factors and psychological factors were able to explain the variability of the variable of 39.8%. While the remaining 60.2% is explained by other variables outside the model. Keywords: cultural factors, social factors, personal factors, psychological factors.